2015
DOI: 10.1371/journal.pone.0128090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-Irradiation at Different Stages in the Cell Cycle on Individual Cell–Based Kinetics in an Asynchronous Cell Population

Abstract: Using an asynchronously growing cell population, we investigated how X-irradiation at different stages of the cell cycle influences individual cell–based kinetics. To visualize the cell-cycle phase, we employed the fluorescent ubiquitination-based cell cycle indicator (Fucci). After 5 Gy irradiation, HeLa cells no longer entered M phase in an order determined by their previous stage of the cell cycle, primarily because green phase (S and G2) was less prolonged in cells irradiated during the red phase (G1) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…This observation indicates that the duration of G2 arrest was strongly dependent on distance from the Ir-192 source, demonstrating that it was primarily influenced by absorption dose. Previous work showed that the duration of G2 arrest is proportional to absorption dose [ 15 , 18 ]; however, in this study, the use of HeLa-Fucci cells allowed us to clearly temporo-spatially visualize this phenomenon, even in the steep dose gradient of an Ir-192 HDR-RALS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This observation indicates that the duration of G2 arrest was strongly dependent on distance from the Ir-192 source, demonstrating that it was primarily influenced by absorption dose. Previous work showed that the duration of G2 arrest is proportional to absorption dose [ 15 , 18 ]; however, in this study, the use of HeLa-Fucci cells allowed us to clearly temporo-spatially visualize this phenomenon, even in the steep dose gradient of an Ir-192 HDR-RALS.…”
Section: Discussionmentioning
confidence: 88%
“…7b ). Because this difference was longer than the normal red phase duration (~8 h) [ 15 ] for cells at 5 mm, the phenomenon described above could be due to cells irradiated in red phase entering M phase faster than those irradiated in green phase. On the other hand, such cases were not clearly observed at 20 mm, because the difference was much smaller than ~8 h. We also analyzed the number of entries into M phase as a function of fluorescence color at irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…DNA content analysis by flow cytometry revealed that cells were released later from G2 arrest after 6 Gy irradiation than after 2 Gy irradiation; however, when irradiation was combined with KPU-300 treatment, no useful information was obtained to explain the difference ( Fig 7Ba ). The elongation of the green phase represents G2 arrest [ 41 ]; therefore, we concluded that G2 arrest was more strongly induced during KPU-300 treatment following 6 Gy irradiation than following 2 Gy irradiation ( Fig 7Ba ). Consequently, the ratio of mitotic cells released from G2 arrest was significantly higher in cells exposed to 2 Gy than in those exposed to 6 Gy ( Fig 7Bb , Fig 7Bc )( S6 Table ).…”
Section: Resultsmentioning
confidence: 93%
“…DSB repair pathways have overlapping roles in DNA repair and are highly dependent on cell cycle phase [ 31 ]. Differential cellular sensitivities to IR have been reported depending on the phase of the cell cycle at the time of irradiation [ 13 ]. Hence, cells are known to be more radioresistant in the early G1 and late S phases and show increased radio sensitivity in the early S phase [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ropolo et al indicated that GSC lines display a significantly elongated cell cycle compared to non-stem cells in response to enhanced activities of the DNA damage checkpoint kinases Chk1 and Chk2 [ 12 ]. Several other studies have reported that the sensitivity of cells to IR varied widely depending on the phase of the cell cycle at the time of irradiation, and have also shown that cells in the G2 and M phases were approximately 3 times more sensitive than cells in the S phase [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%